The Medical Legal Aspects of Surgery First and a New Model of Consent Form. Issue 7 (October 2016) - Pelo, Sandro; Saponaro, Gianmarco; Gasparini, Giulio; De Angelis, Paolo; Spota, Andrea; Garagiola, Umberto; Foresta, Enrico; Moro, Alessandro
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The introduction of "surgery first" has resulted in a new requirement to compare and resolve medical legal problems which previously did not exist in traditional orthognathic surgery. The first issue relates to the relationship between the doctor and the patient and, in particular, the need to create a new informed consent form for surgery first. The second problem that has arisen with the arrival of surgery first concerns the relationship between health workers, namely the surgeon, and the orthodontist. The authors of this article propose a new template for informed consent specifically created for surgery first and also a model for the new working relationship between surgeons and orthodontists which will facilitate and improve co-operation between them. This will improve results, and guarantee a greater level of protection for the surgeon. It will also enable the identification the individual responsibilities of each person.